The relationship between decision making ability and implicit pattern-perception in soccer players - Murakawa, D.; Ikudome, S.; Takai, Y.; Ogasa, K.; Mori, S.; Nakamoto, H. (Japanese Journal of Sport Psychology, 2020)
This study aimed to clarify contribution of implicit pattern perception to decision-making ability in soccer player. To this end, we examined whether the accuracy of implicit pattern-perception of soccer-specific scene differ depending on the soccer player's decision-making ability (Experiment 1) and the influence of the implicitly perceived information on decision-making (Experiment 2). Three coaches classified 30 participants into three groups based on their decision-making ability (high, medium and low). In Experiment 1, images of the soccer scene (3 vs. 3) were presented under five conditions of varying durations (from 17 to 85ms) using a backward-masking method that induces implicit perception. Participants' degree of consciousness to the stimulus was assessed by asking them to indicate the positions of unmarked players (right, left, center, or none), and report their confidence in their response (25% to 100%). Results showed that in the 34ms condition, the correct answers of the high and medium groups were significantly higher than the chance level even though the confidence was only around 25%. In Experiment 2, after presentation of the prime stimuli used in Experiment 1 (17, 34, 85ms), 3 vs. 3 scenes (target stimuli) were presented again until a decision was made. The target stimuli were presented in a congruent or an incongruent manner. The participants also indicated the unmarked player's position in the target stimulus by pressing a button. Here, in the 34ms condition, the difference in the reaction time between congruent and incongruent stimuli was significantly larger only in the high group. These results suggest that skilled decision makers are superior in implicit pattern-perception and soccer players use it for decision-making.